A novel exome probe set captures phototransduction genes across birds (Aves) enabling efficient analysis of vision evolution. (15th October 2021) - White, Noor D.; Batz, Zachary A.; Braun, Edward L.; Braun, Michael J.; Carleton, Karen L.; Kimball, Rebecca T.; Swaroop, Anand
Abstract: The diversity of avian visual phenotypes provides a framework for studying mechanisms of trait diversification generally, and the evolution of vertebrate vision, specifically. Previous research has focused on opsins, but to fully understand visual adaptation, we must study the complete phototransduction cascade (PTC). Here, we developed a probe set that captures exonic regions of 46 genes representing the PTC and other light responses. For a subset of species, we directly compared gene capture between our probe set and low‐coverage whole genome sequencing (WGS), and we discuss considerations for choosing between these methods. Finally, we developed a unique strategy to avoid chimeric assembly by using "decoy" reference sequences. We successfully captured an average of 64% of our targeted exome in 46 species across 14 orders using the probe set and had similar recovery using the WGS data. Compared to WGS or transcriptomes, our probe set: (1) reduces sequencing requirements by efficiently capturing vision genes, (2) employs a simpler bioinformatic pipeline by limiting required assembly and negating annotation, and (3) eliminates the need for fresh tissues, enabling researchers to leverage existing museum collections. We then utilized our vision exome data to identify positively selected genes in two evolutionary scenarios—evolution of night vision in nocturnal birds and evolution of high‐speed vision specific to manakins (Pipridae). We found parallel positive selection of SLC24A1 in both scenarios, implicating the alteration of rod response kinetics, which could improve color discrimination in dim light conditions and/or facilitate higher temporal resolution.